Design and fabrication of spring roll maker / Afiq Rahman Mohammad and Ahmad Najmie Rusli - Mohammad, Afiq Rahman; Rusli, Ahmad Najmie (School of Mechanical Engineering, 2022)
The spring roll also known as “Popia” is regarded as one of the most famous snack choices in Malaysia. It is easy to make, and its ingredients are also cheap but the process of making spring rolls in larger batches can be time-consuming and uses loads of energy. This project aims to design, analyse, and fabricate a Spring Roll Maker that can make as many as spring rolls possible to suit the needs of the user. Three designs will be drawn and analysed to determine the effectiveness of the product and to determine the best material to be used. Then, the final design sketch will be developed into parts and assembled into a complete product using SolidWorks software. The parts will also be analysed using the SolidWorks software. After the suitable materials has been picked, the product will be fabricated using various fabrication processes such as cutting, soldering, and drilling. The finished product is then tested using items that resemble a dough as dough is unobtainable. The product can complete its intended tasks within 1 minute. This shows that the product works as intended. The product shows promising results during testing although the product was not tested with a dough. In conclusion, further tests with a dough are required to determine the efficiency of the product